Application in photocatalytic degradation of zearalenone based on graphitic carbon nitride. (17th November 2021) - Li, Li; Xiaoxue, Shan; Yuchong, Zhang; Jin, Wang; Zilong, Liao; Yuxi, Gu; Shuai, Chen; Youjun, Jiang; Jinying, Chen
Abstract: A semiconductor nano‐material was prepared, and its degradation efficiency of zearalenone (ZEN) was studied. The photocatalytic material graphitic carbon nitride (g‐C3 N4 ) was synthesized by the traditional method of hot cracking. Its structure was characterized by X‐ray diffraction (XRD), Fourier‐transform infrared (FTIR), X‐ray photoelectron spectroscopy (XPS), scanning electron microscopy (SEM) and transmission electron microscopy (TEM). The photocatalytic degradation experiment showed that under the irradiation of ultraviolet (UV) lamp (254 nm, including 185 nm), g‐C3 N4 could induce photocatalytic effect, which provided a new method for the degradation of ZEN in real powder samples. The experimental conditions of photocatalytic degradation of the primary reference material of ZEN and ZEN in real powder samples were explored. And the degradation products of ZEN were analyzed after high‐performance liquid chromatography–mass spectrometry (HPLC–MS). Under each optimal experimental conditions, the degradation rate on primary reference material of ZEN and ZEN in real powder samples was 96.0% and 50.0%, respectively. The results in this work provide a theoretical reference and practical basis for the photocatalytic degradation of mycotoxin in real powder samples by g‐C3 N4 . Abstract : In our work, a semiconductor nano‐material was prepared, and its degradation efficiency towards zearalenone (ZEN) was studied. The photocatalytic degradation experiment showed that under the irradiation of ultraviolet (UV) lamp with the 254 nm wavelength (including 185 nm), graphitic carbon nitride (g‐C3 N4 ) could induce photocatalytic effect, and decompose ZEN, providing a novel approach for the degradation of ZEN in real powder samples.